Hospital discharge process in a neonatal unit from the point of view of the healthcare team - Danielle Bonotto Cabral Reis; Adriana Duarte Rocha (Revista Enfermagem Digital Cuidado e Promoção da Saúde)
OBJECTIVE: To find out how the multiprofessional team understands neonatal hospital discharge and to analyze the participation of health professionals in the hospital discharge process in a reference neonatal unit. METHOD: Qualitative and exploratory study with 41 health professionals from a neonatal unit. Semi-structured interviews were used to collect data, and content analysis according to Bardin (2016) was used to process the data. RESULTS: Four categories emerged: transfer of care: from the neonatal unit to the home; newborn-centered care focused on hospital discharge; the medical professional as the centralizer of hospital discharge; and hospital discharge seen as a process. FINAL CONSIDERATIONS: This study showed that the multi-professional team understands discharge as a process of transferring care of the newborn. The majority of professionals, although actively involved in the discharge process, see the doctor as the centralizing figure.